Social Family Support for Children With Special Needs in Special School Care for Nagari Children, Akabiluru District - saputri kelana (Journal of Social Research, 2022)
Background: Children are a gift from Allah SWT which is entrusted to parents.   Objective: aims to understand social reality, namely seeing the world from what it is, not the world that people should have an open minded nature, because doing qualitative research properly and correctly means having a window to understand the world of psychology and social reality.   Methods: This research is descriptive qualitative, namely a method that describes the conditions that occur in the field in the form of words or not in the form of numbers.   Results: the results of the research that the author has done through interviews and observations to key informants, namely 2 parents of children with special needs and the supporting informants are 2 children with special needs with 2 types of special needs, namely mentally retarded children and autistic children and teachers in Special Schools Caring for Nagari Children, Akabiluru District.   Conslusion: that family social support for children with special needs at the Nagari Children's Care Special School, Akabiluru District.